UNED: Needed reevaluation to face historical changes and three socio-demographic characteristics of its graduations (National Administration Journal, 2019)
This article portrays the historical  transformations in the world and  in Costa  Rica,  since 1977,  date  of creation of the UNED, to emphasize how its foundational objectives acquire greater relevance inthe  current conditions,   when   social  gaps havebeen  accentuated, the  transcendence  of having university studies and revolutionizing the technologies proper to  its  educational modality have been revolutionized. There is a gap betweenthese processes and the strategic weight of the UNED, which has remained unchanged since its foundation. Costa Rica's successful but unfinished model  of internationalization, immersed  as  it  isin globalization, has also caused a loss of social cohesion. With  the analysis  of  the profiles  of secondaryeducation,  socio-geographic   origin and gender of its graduates, the role of the UNED is emphasized  as  a public  educational  policy  of convergence between the existing socioeconomic contrasts. This shows the relevance of the UNED and advocates the revaluation of its strategic role.
Keywords: UNED; Education; Distance Education; Social Cohesion; Convergence Policies; Development Model